2015
DOI: 10.1016/j.ccell.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Iron Trafficking Characterizes Glioblastoma Stem-like Cells

Abstract: Summary Glioblastomas display hierarchies with self-renewing cancer stem-like cells (CSCs). RNA sequencing and enhancer mapping revealed regulatory programs unique to CSCs causing upregulation of the iron transporter transferrin, the top differentially expressed gene compared to tissue-specific progenitors. Direct interrogation of iron uptake demonstrated CSCs potently extract iron from the microenvironment more effectively than other tumor cells. Systematic interrogation of iron flux determined that CSCs pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
276
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(318 citation statements)
references
References 55 publications
20
276
1
4
Order By: Relevance
“…In the US population, the two most common polymorphisms in HFE , H63D and C282Y , are seen in approximately 15% and 7% of the population, respectively [35]. Interestingly, recent work has also shown that the expression of TfR is a poor prognostic indicator in GBM, and that dysregulated iron metabolism including increased TfR expression and ferritin expression is associated with cancer stem cells in GBM [36] This suggests that the gene signature identified here is, at least in part, sorting cancers with more robust stem cell populations from cancers with fewer cancer stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the US population, the two most common polymorphisms in HFE , H63D and C282Y , are seen in approximately 15% and 7% of the population, respectively [35]. Interestingly, recent work has also shown that the expression of TfR is a poor prognostic indicator in GBM, and that dysregulated iron metabolism including increased TfR expression and ferritin expression is associated with cancer stem cells in GBM [36] This suggests that the gene signature identified here is, at least in part, sorting cancers with more robust stem cell populations from cancers with fewer cancer stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…7). Previous reports on ferritin-induced growth signaling described how glioblastoma cancer cells had high ferritin levels due to increased iron intake (10). In contrast, we demonstrate how cancer cells use an electrophilic oncometabolite to hijack ferritin regulation in an iron-independent mechanism to increase ferritin levels.…”
Section: Discussionmentioning
confidence: 42%
“…6F), indicating that ferritin can mediate growth in UOK262 cells. Previous reports indicated that FOXM1 was activated by ferritin through STAT3 signaling (10). Although UOK262-FH Ϫ/Ϫ cells had increased STAT3 phosphorylation relative to UOK262-FH res cells (see Fig.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations